Effect Module Based Education on Mothers’ Knowledge of Stunting Prevention: A Pre - Post Study - Sah Puteri, Sri Kurnia; Sumarmi; Nuryana, Riska; Mantasia; Hermadin; Hartati (Omni Health Journal, 2026)
Background: Stunting is a chronic growth disorder caused by long-term inadequate nutritional intake, particularly during the first 1,000 days of life. This condition does not occur at birth but develops over time and becomes evident as impaired linear growth in children under five years of age. Objective: This study aimed to assess mothers’ knowledge regarding stunting prevention before and after the provision of module-based education in Sanrobone Village, Takalar Regency. Methods: This study used a quantitative descriptive design with a pre–post approach. The population and sample consisted of 62 pregnant women selected using total sampling. Data were collected using a structured questionnaire administered before and after the educational intervention. Results: Before the intervention, 17 respondents (27.4%) had good knowledge, while 45 respondents (72.6%) had poor knowledge. After the intervention, the proportion of respondents with good knowledge increased to 37 (59.6%), while those with poor knowledge decreased to 25 (40.4%). These findings indicate a clear improvement in maternal knowledge following the educational intervention. Conclusion: Module-based education effectively improves mothers’ knowledge regarding stunting prevention. Strengthening educational interventions at the community level is essential to support early prevention efforts and improve child health outcomes.